1999
DOI: 10.1164/ajrccm.160.2.9812078
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Levels Correlate with the Severity and the Mortality of Primary Pulmonary Hypertension

Abstract: Serum uric acid (UA), the final product of purine degradation, has been proposed to be a marker for impaired oxidative metabolism and a possible predictor of mortality in patients with chronic heart failure. To elucidate whether serum UA correlates with the severity and the mortality of primary pulmonary hypertension (PPH), serum UA was assessed in 90 patients with PPH together with other clinical variables. Right heart catheterization was performed in all patients. Serum UA was significantly elevated in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
167
2
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(189 citation statements)
references
References 29 publications
12
167
2
8
Order By: Relevance
“…Elevated uric acid levels have long been known to be a poor prognostic sign in acute illness [51]. Several studies have demonstrated that an elevated urate level in PH correlates with severity of disease [52][53][54][55][56]. In one study, 90 patients with IPAH underwent right heart catheterisation and serum uric acid estimation, and were then followed for a mean of 31 months [54].…”
Section: Uric Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated uric acid levels have long been known to be a poor prognostic sign in acute illness [51]. Several studies have demonstrated that an elevated urate level in PH correlates with severity of disease [52][53][54][55][56]. In one study, 90 patients with IPAH underwent right heart catheterisation and serum uric acid estimation, and were then followed for a mean of 31 months [54].…”
Section: Uric Acidmentioning
confidence: 99%
“…A number of studies have sought to define the prognostic value of biomarkers in PH. Several markers have been shown to be independent predictors of mortality in PAH, including serum uric acid [54], BNP [10] and NT-proBNP [28]. Cardiac troponin T is an independent predictor of mortality in patients with PH of various classes [58], and in sickle cell disease elevated NT-proBNP is a major risk factor for death [34].…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…Higher vWF levels at baseline and despite therapy are independently associated with an increased risk of death in PAH [60]. Similarly, a variety of biomarkers tied to cardiac function have been investigated in PAH [38,50,63,64]. The best studied, natriuretic peptides are produced by the cardiac atria and ventricles in response to myocyte stretch and may serve as endocrinologic indicators of heart function.…”
Section: Plasma Biomarkersmentioning
confidence: 99%
“…In recent years, it has become of growing importance to have precise early and convenient method to diagnose PAH in SCD [7]. Several biomarkers such as brain natriuretic peptide [8], endothelin-1 9 (ET1) and UA [10][11][12] were found to have good correlations in patients with PAH. However, the association between UA and PAH in SCD is unknown.…”
Section: Introductionmentioning
confidence: 99%